Short-term safety, tolerability and efficacy of a very low-calorie-ketogenic diet interventional weight loss program versus hypocaloric diet in patients with type 2 diabetes mellitus - Goday, A; Bellido, D; Sajoux, I; Crujeiras, A B; Burguera, B; García-Luna, P P; Oleaga, A; Moreno, B; Casanueva, F F (Nutrition & diabetes, 2016)
Brackground: The safety and tolerability of very low-calorie-ketogenic (VLCK) diets are a current concern in the treatment of obese type 2 diabetes mellitus (T2DM) patients. Objective: Evaluating the short-term safety and tolerability of a VLCK diet (<50 g of carbohydrate daily) in an interventional weight loss program including lifestyle and behavioral modification support (Diaprokal Method) in subjects with T2DM. Methods: Eighty-nine men and women, aged between 30 and 65 years, with T2DM and body mass index between 30 and 35 kg m − 2 participated in this prospective, open-label, multi-centric randomized clinical trial with a duration of 4 months. Forty-five subjects were randomly assigned to the interventional weight loss (VLCK diet), and 44 to the standard low-calorie diet. Results: No significant differences in the laboratory safety parameters were found between the two study groups. Changes in the urine albumin-to-creatinine ratio in VLCK diet were not significant and were comparable to control group. Creatinine and blood urea nitrogen did not change significantly relative to baseline nor between groups. Weight loss and reduction in waist circumference in the VLCK diet group were significantly larger than in control subjects (both P <0.001). The decline in HbA1c and glycemic control was larger in the VLCK diet group ( P <0.05). No serious adverse events were reported and mild AE in the VLCK diet group declined at last follow-up. Conclusions: The interventional weight loss program based on a VLCK diet is most effective in reducing body weight and improvement of glycemic control than a standard hypocaloric diet with safety and good tolerance for T2DM patients.